Optimizing for a variety of issues can advance genetic gain and lower emission intensity in the community-based breeding programs - Getachew, Tesfaye; Mueller, Jack; Rekik, Mourad; Rischkowsky, Barbara; Gizaw, Solomon; Belay, Berhanu; Haile, Aynalem (International Center for Agricultural Research in the Dry Areas, 2023)
Optimizing for a variety of issues can advance genetic gain and lower emission intensity in the community-based breeding programs.